2011
DOI: 10.1039/c1sm05350g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of poly(glycerol sebacate)-co-lactic acid as surgical sealants

Abstract: Surgical sealants are currently used in conjunction with sutures to reduce the incidence of air or fluid leaks. Although fibrin and collagen sealants can effectively promote wound healing, there are serious concerns about blood-borne virus contamination. Hence, synthetic sealants have been considered a safer alternative. In this work, a new family of synthetic surgical sealant copolymers were derived from poly(glycerol sebacate) (PGS) and lactic acid (LA). The newly developed PGS-co-LA tissue sealants had sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 35 publications
3
51
0
Order By: Relevance
“…For example, Chen et al . developed a surgical sealant based on poly(glycerol sebacate) (PGS) and lactic acid (LA) [3]. The use of LA improved the cytocompatibility of the engineered sealant compared to PGS alone.…”
Section: Synthetic Polymer Derived Elastic Sealantsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Chen et al . developed a surgical sealant based on poly(glycerol sebacate) (PGS) and lactic acid (LA) [3]. The use of LA improved the cytocompatibility of the engineered sealant compared to PGS alone.…”
Section: Synthetic Polymer Derived Elastic Sealantsmentioning
confidence: 99%
“…The sealant could be applied at 45 °C and solidified at 37 °C to form an elastic gel by exposing to a cold gas. It was shown that the fabricated sealant had higher adhesion strength to the tissues compared to both fibrin glues and synthetic sealants such as Pleuraseal [3]. Photocurable elastomers based on PGS with strain between 42–189% and Young Modulus of 0.05–1.38 MPa were also developed through acrylation of PGS [21].…”
Section: Synthetic Polymer Derived Elastic Sealantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyglycerol sebacate (PGS), a biodegradable elastomer, has been extensively evaluated for a broad range of applications in regenerative medicine including cardiovascular patches (Chen et al , 2008), vascular tissue grafts (Motlagh et al , 2006), engineered heart valves (Masoumi et al , 2013), cartilage tissues (Kemppainen and Hollister, 2010), nerve conduits (Sundback et al , 2005), retinal implants (Pritchard et al , 2010), and surgical sealants (Chen et al , 2011). Such diverse applications are primarily attributed to the controlled degradation profile, non-toxic byproducts and highly elastomeric nature of PGS (Rai et al , 2012; Wang et al , 2003a; Wang et al , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…PGS is the most widely studied PPS member [4,8,[21][22][23][24]. The Young's modulus of PGS is in the range of 0.05-1.5MPa [25].…”
Section: Introductionmentioning
confidence: 99%